Changes in Flow Density Measured Using Optical Coherence Tomography Angiography after iStent Insertion in Combination with Phacoemulsification in Patients with Open-Angle Glaucoma - Maged Alnawaiseh; Viktoria Müller; Larissa Lahme; Ralph Laurent Merté; Nicole Eter (Journal of Ophthalmology)
Purpose. To evaluate changes in flow density after the implantation of a trabecular microbypass stent (iStent) in combination with cataract surgery. Methods. A total of 48 eyes of 48 patients, who underwent either cataract surgery alone (cataract group) or cataract surgery with implantation of two iStent inject devices (iStent group), were prospectively included in this study. Intraocular pressure (IOP) and flow density data before and after surgery were extracted and analyzed. Results. In the iStent group, the mean IOP was 18.2 ± 3.3 mmHg prior to surgery and 13.2 ± 2.3 at follow-up, and this difference was statistically significant (p<0.001). The mean IOP in the cataract group also improved significantly after surgery (before: 17.1 ± 2.4; after: 15.1 ± 2.7 p=0.003). The flow density (whole en face) in the superficial and deep retinal OCT angiogram of the macula (superficial: p=0.002; deep: p=0.034) and in the ONH (p=0.011) improved significantly after surgery in the iStent group. The differences in the cataract group were not significant. Conclusions. Flow density of the macula and ONH, as measured by OCTA, improved significantly after cataract surgery with iStent. Noninvasive quantitative analyses of flow density provide a new parameter, which can help for the monitoring of therapy success after glaucoma surgery.